Mr. Gaga: Embodying the Exceptionalism of Ohad Naharin - Quinlan, Meghan (The International Journal of Screendance, 2019)
The life and work of Israeli choreographer Ohad Naharin are documented in the 2015 film by Tomer Heymann, Mr. Gaga. With nearly a decade of footage from following Naharin’s work with the Batsheva Dance Company, the documentary celebrates Naharin’s life with abundant footage from his choreographic successes. This article explores the ways in which this film, like many dance documentaries, uses dance footage in strategic ways to present dance artists as exceptional. In Mr. Gaga in particular, the national and cultural specificity of the story and footage portrayed in the film require critical analysis to better understand subtle political undertones and bias embedded in the film’s otherwise primarily aesthetic focus.